Evaluasi Kinerja Elektrokimia Katoda LiFePO4 dengan Variasi Aditif Graphene Oxide, Reduced Graphene Oxide dan Koloid Nanopartikel Perak (AgNP) - Agun Pranata; Delovita ginting; Romi Fadli Syahputra (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
The low electronic conductivity of Lithium Iron Phosphate (LFP) cathodes presents a major challenge for their application in lithium-ion batteries. This research aims to enhance the electrochemical performance of LFP by comparing the effects of three different conductive additives: Graphene Oxide (GO), reduced Graphene Oxide (rGO), and a Silver Nanoparticles (AgNP) composite. GO was synthesized from graphite powder via a modified Hummers’ method, followed by the fabrication of three cathode variations. Material characterization was performed using X-Ray Diffraction (XRD), UV-Diffuse Reflectance Spectroscopy (UV-DRS), and Cyclic Voltammetry (CV). XRD analysis confirmed the successful synthesis of GO, evidenced by the shift of the main diffraction peak from 26.24° in graphite to 9.80° in GO. Band gap (Eg) analysis from UV-DRS data showed that the addition of rGO and the AgNP effectively reduced the Eg value to 2.91 Ev and 2.73 Ev, respectively, from the initial value of 3.10 Ev for the LFP+GO sample. Electrochemical tests indicated that the LFP+rGO cathode exhibited the most significant current response, achieving the highest specific capacitance of 5.0 F/g at a scan rate of 5 Mv/s. These results confirm that rGO is the most effective additive among the three variations for enhancing the electrochemical properties of LiFePO4 cathodes. Keywords: LiFePO₄, Graphene Oxide, Reduced Graphene Oxide, Silver Nanoparticles, Specific Capacitance.